Optimisation of histamine reduction in kawakawa (Euthynnus Affinis) by red apple juice using response surface methodology (RSM) / Zuliana Razikin - Razikin, Zuliana (Faculty of Applied Sciences, 2008)
Histamine in fish can cause allergic reactions in people ranging from mild skin discomfort to nausea, vomiting and diarrhea. This study has been done to reduce histamine in kawakawa (Euthynnus Affinis) by using red apple juice that content quercetin known as histamine production's inhibitor. Response Surface Methodology (RSM) of MINITAB Software Version 14 has been used to create experimental design for analysis whereby concentration of red apple juice, temperature and time of immersion were used as variables. Samples treated were derivative with o-pthaldehyde (OPA) before analysed. Histamine analysis was carried out according to AOAC Official Method 1990 and measured using spectrofluorometer. Results showed that histamine reduction was optimised at 93.59% of red apple juice concentration, -0.78°C of immersion temperature for 15.82 hours.